The Plant Phenology Ontology: A New Informatics Resource for Large-Scale Integration of Plant Phenology Data - Stucky, Brian J.; Guralnick, Rob; Deck, John; Denny, Ellen G.; Bolmgren, Kjell; Walls, Ramona (Frontiers in Plant Science, 2018)
Plant phenology – the timing of plant life-cycle events, such as flowering or leafing out – plays a fundamental role in the functioning of terrestrial ecosystems, including human agricultural systems. Because plant phenology is often linked with climatic variables, there is widespread interest in developing a deeper understanding of global plant phenology patterns and trends. Although phenology data from around the world are currently available, truly global analyses of plant phenology have so far been difficult because the organizations producing large-scale phenology data are using non-standardized terminologies and metrics during data collection and data processing. To address this problem, we have developed the Plant Phenology Ontology (PPO). The PPO provides the standardized vocabulary and semantic framework that is needed for large-scale integration of heterogeneous plant phenology data. Here, we describe the PPO, and we also report preliminary results of using the PPO and a new data processing pipeline to build a large dataset of phenology information from North America and Europe.